Planning institutions as gatekeepers in housing production in Lagos, Nigeria. Issue 5 (4th July 2018) - Alabi, Moruf; Bako, Abdulateef
ABSTRACT: In every phase of housing production, there are certain "gatekeepers" that constrain access to housing resources. This article argues that the activities of physical planning institutions constrain access to residential building permits in Lagos, Nigeria. From May 2013 to May 2014, 7, 281 residential structures were served with contravention notices while only 1, 380 applications for residential building plans were approved in 2013. This figure is negligible in relation to the population of Lagos and its housing needs. There is therefore a need to review the criteria for granting residential building permits to encourage participation from the informal private sector.